The house of Dies Drear - Hamilton, Virginia (New York Aladdin paperbacks, 1984)
An African American family tries to unravel the secrets of their new home in Ohio which was once an important station on the Underground Railroad.
Keywords: Mystery and detective stories; African Americans -- Juvenile fiction; African Americans -- Fiction; Underground railroad -- Fiction; Ohio -- History -- 20th century -- Fiction